Population dynamics of the gall inducer Eriogallococcus isaias (Hemiptera: Coccoidea: Eriococcidae) on Pseudobombax grandiflorum (Malvaceae) - Magalhães, Thiago A.; Oliveira, Denis C.; Isaias, Rosy M. S. (Journal of natural history, 2015)
Eriogallococcus isaias Hodgson and Magalhães is a Neotropical species of gall-inducing scale insect (Coccoidea: Eriococcidae), whose phenological synchrony with its host plant, Pseudobombax grandiflorum, is fundamental to the maintenance of its population. Furthermore, E. isaias is unusual among gall-inducing Eriococcidae because its galls are not sexually dimorphic and are induced by the second-instar nymphs. We studied the life cycles of the host plant and the galling insect, and followed the development of the insects and the structure of the gall. The results showed that gall induction is synchronous with leaf flushing, and that the galls and leaves mature concomitantly. Males have a 36-48-day life cycle within the gall, whereas females have a 75-100-day life cycle.